The independent pulsations of Jupiter's northern and southern X-ray auroras. (November 2017) - Dunn, W.; Branduardi-Raymont, G.; Ray, L.; Jackman, C.; Kraft, R.; Elsner, R.; Rae, I.; Yao, Z.; Vogt, M.; Jones, G.; Gladstone, G.; Orton, G.; et al.
Abstract Auroral hot spots are observed across the Universe at different scales1 and mark the coupling between a surrounding plasma environment and an atmosphere. Within our own Solar System, Jupiter possesses the only resolvable example of this large-scale energy transfer. Jupiter's northern X-ray aurora is concentrated into a hot spot, which is located at the most poleward regions of the planet's aurora and pulses either periodically2, 3 or irregularly4, 5 . X-ray emission line spectra demonstrate that Jupiter's northern hot spot is produced by high charge-state oxygen, sulfur and/or carbon ions with ﻿an energy o﻿f tens of MeV (refs4–6 ) that are undergoing charge exchange. Observations instead failed to reveal a similar feature in the south2, 3, 7, 8 . Here, we report the existence of a persistent southern X-ray hot spot. Surprisingly, this large-scale southern auroral structure behaves independently of its northern counterpart. Using XMM-Newton and Chandra X-ray campaigns, performed in May–June 2016 and March 2007, we show that Jupiter's northern and southern spots each exhibit different characteristics, such as different periodic pulsations and uncorrelated changes in brightness. These observations imply that highly energetic, non-conjugate magnetospheric processes sometimes drive the polar regions of Jupiter's dayside magnetosphere. This is in contrast to current models of X-ray generation for Jupiter9, 10 . Understanding the behaviour and drivers of Jupiter's pair of hot spots is critical to the use of X-rays as diagnostics of the wide range of rapidly rotating celestial bodies that exhibit these auroral phenomena. The authors discover that Jupiter's southern X-ray aurora is concentrated into a hot spot (until now only the north pole was known to have one), which behaves completely differently in brightness and timing pulsation from its northern counterpart.